CHARACTER FEATURES FOR WOMEN WITH UROLITHIASIS ILLNES AND THEIR PSYCHOCORRECTIC SUPPORT - G. Moysik; L. Trachuk; O. A. Golotsvan (Bogomolets National Medical University, 2015)
Summary. The article describes research on the nature, level of alexithymia in patients with urolithiasis in women, the influence of autogenous training on the general condition of these patients. Also, the article describes a plan psychic correction support female patients with urolithiasis on the basis of the study data. Features character study were using the technique MMPI mini-mult. Based on the results, it is evident impact of physical illness to specific changes in nature: in patients with long course of urolithiasis compared to the control group are more pronounced manifestations isteroyidnosti, psychasthenia, schizoid. The level of alexithymia was determined using Torontivskoho aleksytymichnoho test. Results of the test found that among patients with urolithiasis compared to the control group higher level of alexithymia. Relaxation technique was performed by Schulz to patients. Effect of autogenous training on the overall functional state of mind, the mood was determined by a test Luscher. The results indicate a reduction in anxiety levels, compensation for stress, improve mood in patients with urolithiasis after autogenous training. Based on the survey results, taking into account identified in the study traits of women with urolithiasis, these patients recommended psycho support in the form of art therapy, body-oriented therapy, relaxation techniques, group and individual therapy to reduce the level of alexithymia, reducing and isteroyidnosti compensation manifestations, psychasthenia, schizoid. An integrated approach of medication, physical therapy and psychocorrection support will help, healing patients.